The Influence of Lifestyle and Paylater Usage on Consumption Behavior: A Review of Islamic Economics (Case Study of Generation Z in Medan City) - Ade Vitria; Tri Inda Fadhila Rahma; Nursantri Yanti (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study seeks to determine the impact of the use of a deferred payment system (paylater) on the consumption behavior of Generation Z in the field of Islamic Economics, the impact of a hedonistic lifestyle on Islamic Economic consumption behavior among Generation Z E-Commerce users in Medan City, and the interaction between the use of a deferred payment system and a hedonistic lifestyle on the consumption behavior of Generation Z. The research method used is quantitative research with a survey approach. Data were collected through a Likert-scale-based questionnaire to 120 Muslim Generation Z respondents who use paylater in Medan City. Data analysis was carried out using multiple linear regression tests using SPSS statistical software, with instrument validity and reliability tests that have been carried out previously. The results of the study indicate that lifestyle and the use of paylater have a positive and significant effect on the consumption behavior of Generation Z. A positive relationship, so that this modern lifestyle and hedonistic attitude ultimately increase excessive consumption behavior. Therefore, the importance of Islamic Economic literacy in fostering responsible consumption behavior in the digital era.